Comparison of diagnostic yield of GeneXpert MTB/RIF assay and ZN (Ziehl-Neelsen) staining in serosal fluids from HIV and non-HIV patients with extra-pulmonary tuberculosis - Mittal, Mahim; Kumar, Ritesh (International Journal of Research in Medical Sciences, 2017)
Background: India accounts for 23% of the global TB burden and of these 15-20% are extrapulmonary tuberculosis(EPTB). EPTB has diverse clinical presentation and often is over diagnosed because of lack of standardised diagnostic means. Yield of acid fast bacilli (AFB) from EPTB settings is very low and alternate facilities are nearly non-existent routinely. GeneXpert MTB/RIF has been recommended as a diagnostic tool for sputum samples. It has been also recommended for serosal fluids from HIV patients only. This study was done to compare the yield of GeneXpert MTB/RIF assay and ZN (Ziehl Neelsen) staining among HIV and non-HIV patients with suspected serosal TB. Methods: GeneXpert MTB/RIF assay and ZN staining was done in all serosal fluid samples in which a clinical diagnosis of serosal TB had been made by conventional methods. Results: A total of 81 extra pulmonary samples (21 from HIV and 60 from non-HIV patients) were processed in this study, which included 48 CSF, 19 pleural fluids and 14 ascitic fluid. Out of these, 34.5% (28/81) patients were both GeneXpert MTB/RIF as well as ZN stain positive whereas only 13.58%(11/81) patients were ZN stain positive. 4/21 (19.05%) samples from HIV patients were ZN stain positive and 9/21(42.85%) were GeneXpert positive. 7/60 (11.66%) samples from non-HIV patients were ZN stain positive and 19/60 (31.66%) were GeneXpert positive. Conclusions: GeneXpert MTB/RIF is more sensitive than ZN staining in EPTB. The yield in both HIV and non-HIV patients is the same.